Selection Of Sugarcane Clones From Polycross In Ratoon Cane (Rc) - Sri Yulaikah; Anik Herwati; Mulyani Mulyani; Dian Hariyanto; Moch. Sohri; Slamet Slamet; Imam Santoso; Dewi Utari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Sugar productivity in Indonesia is still low, so it is unable to meet national sugar needs. The use of superior varieties with high productivity is needed to increase sugar productivity. New superior varieties can be obtained through cultivating varieties either by crossing or transgenic methods. The study aimed at evaluating clones resulting from polycross on ratoon cane (RC) with higher crystal yields than their parents (SIL 04). It was carried out at the IP2TP Karangploso Experimental Garden, Sweetener and Fiber Crop Research Institute, Malang, East Java, from January 2021 to December 2021. Eleven crossed clones and one female parent clone (SIL 04) were arranged in a Randomized Block Design with two replications. The results showed 8 clones resulting from the cross (MLG 19/P6/10, MLG 19/P6/11, MLG 19/P6/12, MLG 19/P6/13, MLG 19/P6/16, MLG 19/P6/5, MLG 19/P6/6 and MLG 19/P6/8) produced higher crystal (6.06-7.0 t/ha) than SIL 04 (5.66 t/ha). Improving the crystal structure in the clones resulting from the cross can be done by improving the productivity of sugarcane.